UNLOCKING FLUENT SPEECH: ENHANCING STUDENTS' SPEAKING SKILLS (A CASE STUDY AT JEUMALA AMAL ISLAMIC BOARDING SCHOOL) - Fitri, Mulia; Fauziah; Farizawati (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Speaking skills are essential for students, especially in Islamic boarding schools where daily conversations are prevalent. Students become more engaged in speaking English by emphasizing daily vocabulary memorization, particularly when influenced by equally motivated friends. This research aims to identify the factors that impact students' speaking performance in Islamic boarding school using a qualitative descriptive method. The data was collected through interviews, revealing that motivational factors and the language used in communication significantly influence students' speaking abilities. This study found that requiring students to speak English at Islamic boarding schools helps them become more proficient in speaking. Hence, students' daily activities at Jeumala Amal Islamic boarding school can be utilized to enhance their speaking skills.